2019
DOI: 10.1111/tmi.13221
|View full text |Cite
|
Sign up to set email alerts
|

Caregiver socioemotional health as a determinant of child well‐being in school‐aged and adolescent Ugandan children with and without perinatal HIV exposure

Abstract: Objective Caregiver socio‐emotional attributes are major determinants of child well‐being. This investigation in vulnerable school‐aged Ugandan children estimates relationships between children's well‐being and their caregiver's anxiety, depression and social support. Methods Perinatally HIV‐infected, HIV‐exposed uninfected and HIV‐unexposed Ugandan children and their caregivers were enrolled. Perinatal HIV status was determined by 18 months of age using DNA‐polymerase chain‐reaction test; status was confirmed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 47 publications
1
15
0
Order By: Relevance
“…The inverse association between child psychosocial stress and childreported QOL is reinforced by (a) observation of corresponding inverse association between objectively measured physiologic stress and child reported QOL and (b) negative associations between dependent children' s QOL and their caregivers' levels of acute, recent, and lifetime stress. These findings are in line with the prior reports establishing the importance of caregivers' socioemotional state for wellbeing of their dependent children (Webster et al, 2019). Of importance, association of toxic stress with child wellbeing in this sample was dose dependent and clinically significant with effect sizes often in excess of 0.5 standard deviations regardless of respondent (Norman et al, 2003).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The inverse association between child psychosocial stress and childreported QOL is reinforced by (a) observation of corresponding inverse association between objectively measured physiologic stress and child reported QOL and (b) negative associations between dependent children' s QOL and their caregivers' levels of acute, recent, and lifetime stress. These findings are in line with the prior reports establishing the importance of caregivers' socioemotional state for wellbeing of their dependent children (Webster et al, 2019). Of importance, association of toxic stress with child wellbeing in this sample was dose dependent and clinically significant with effect sizes often in excess of 0.5 standard deviations regardless of respondent (Norman et al, 2003).…”
Section: Discussionsupporting
confidence: 92%
“…This observation is reassuring in the era of universal HAART and confirms previous observation of no caregiver HIV-status related difference in psychosocial adjustment of Ugandan children. (Webster et al, 2019) As would be expected, the vast majority of caregivers in this study were female (mothers). We did not have sufficient number of primary male caregivers to robustly evaluate similarity in wellbeing by male caregiver status.…”
Section: Discussionmentioning
confidence: 50%
“…However, comparative studies for the quality of life of HEU children with HUU children are limited. Two studies from Uganda showed similar quality of life profiles among HUU and HEU children [27,29]. Another study from Uganda found that infection/ exposure predicted low self-esteem and diminished positive outlook in the long term [28].…”
Section: Introductionmentioning
confidence: 96%
“…Previous studies in sub-Saharan Africa have described NCD comorbidities in adults living with HIV [44,[109][110][111][112]. Besides mental health [113][114][115][116][117][118][119][120][121] and lung diseases [122][123][124][125][126], few studies have assessed the prevalence of NCDs and particularly NCD risk factors in AYLHIV in SSA other than as incidental ndings [127][128][129][130][131][132][133][134]. Risk behaviour research on AYLHIV in sub-Saharan Africa has predominantly focused on sexual risk behaviour [135].…”
Section: Discussionmentioning
confidence: 99%